Pelatihan Sistem Informasi Penilaian Siswa Berbasis Web bagi Kelompok Guru Rumah Qur'ani Imam Bukhari di Kabupaten Gowa, Sulawesi Selatan - Siska Anraeni; Harlinda Lahuddin; Andi Alfian Pratama Putra; Rifqatul Mukarramah; Nur Hikmah Amir (Universitas Mathla'ul Anwar Banten, 2020)
TRAINING OF WEB BASED STUDENT ASSESSMENT INFORMATION SYSTEM FOR TEACHER GROUP OF RUMAH QUR'ANI IMAM BUKHARI IN GOWA REGENCY, SOUTH SULAWESI. The activities of the student assessment system at the Rumah Qur'ani Imam Bukhari (RQIB) of Gowa Regency are still conventional. Students also have to wait a long time to find out their grades. Because they have to wait for the homeroom teacher to distribute the daily test papers and assignments students. Therefore, the lecturer team offers solutions including providing counseling for RQIB partners on student assessment information systems, providing simulations about implementing online-based student assessment information systems in processing final grade data, and activating an assessment information system site students at partner schools. The target achieved from this community service activity is that the RQIB student assessment system service site has been activated. Then the counseling and simulation systems have been implemented for teacher group partners. So that, it can help partners quickly and easily to manage student final grade data.